Formulation Emulgel Ethanol Extract of Mullberry (Morus alba L.) with Various Concentration Span 80® dan Tween 80® - Andi Nur Aisyah; Zulham Zulham; Nurul Arfiyanti Yusuf (STIFA Makassar, 2017)
The research about formulation emulgel of mulberry (Morus alba) ethanol extract with various concentrations of emulsifier span and tween 80® has been conducted. The purpose of this study was to determine the concentration of emulsifier (2, 3, 4, and 5%) which resulted stable formulation. Stability testing was performed under two conditions, before and after accelerated storage for 10 cycles with physical parameters include: organoleptic, homogeneity, dispersive power, adhesion, pH and viscosity. The results of showed that all parameters change after accelerated storage, but only F3 showed no significantly difference in before and after storage.